Pengaruh Model Pembelajaran Radec Berbantuan Autograph Ditinjau Dari Kemampuan Literasi Matematik Siswa Di Sekolah Penggerak Pada Materi Persamaan Kuadrat - Dewi Fachraini; Anim Anim (Universitas Asahan, 2026)
The Effect of the Autograph-Assisted RADEC Learning Model in terms of the Mathematical Literacy Ability of Class X Students in the Driving School on the Quadratic Equation Material. The purpose of this study was to determine whether there was an influence in the application of the Autograph-assisted RADEC learning model in terms of the mathematical literacy abilities of class X students in the driving school on the quadratic equation material. This type of research is pre-experimental with one pretest-posttest research design. The population in this study were all class X which consisted of 3 classes. The research sample only had 1 class, namely class X-1 with purposive sampling. Previously, students were given a pretest, which obtained an average of 68.23. After that, students will be given treatment in the form of learning by applying the signature-assisted RADEC learning model. After the learning was completed, the posttest score was obtained with an average value of 85.55. The results of the T test obtained that tcount is 11.330 and ttable at a significance of a = 0.05 is 1.68 so that tcount > ttable (11.330 > 1.68), which means H0 is rejected and H1 is accepted. Thus the effect of the autograph-assisted RADEC learning model on the mathematical literacy ability of class X students in the driving school on the quadratic equation material is obtained.